FEATURES OF CHILDREN'S VOICE DEVELOPMENT IN VOCAL LESSONS - Alimbekova Oydin (Web of Journals Publishing, 2025)
This article analyzes the characteristic aspects of working with a vocal ensemble, including methods and approaches to interaction with performers of different age categories. Special attention is paid to the vocal characteristics of children's and adolescent voices, as well as methods of preparing a musical piece, taking into account the age-related features and individual capabilities of the performer. Key stages of repertoire mastery are also examined in detail.
Keywords: Vocal, vocal ensemble, vocal hearing, children's vocal, vocal technique.